2022
DOI: 10.3390/nano13010166
|View full text |Cite
|
Sign up to set email alerts
|

Nanorod-like Structure of ZnO Nanoparticles and Zn8O8 Clusters Using 4-Dimethylamino Benzaldehyde Liquid to Study the Physicochemical and Antimicrobial Properties of Pathogenic Bacteria

Abstract: To study their physicochemical and antimicrobial properties, zinc oxide nanoparticles were synthesized using a simple chemical route and 4-dimethylaminobenzaldehyde (4DB) as an organic additive. ZnO nanoparticles were characterized with XRD analysis, which confirmed the presence of a hexagonal wurtzite structure with different crystalline sizes. The SEM morphology of the synthesized nanoparticles confirmed the presence of nanorods in both modifications of ZnO nanoparticles. EDS analysis proved the chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
2
1
0
Order By: Relevance
“…The NPs' activity could be initiated in two ways: by directly or electrostatically interacting with the NPs and causing injury to the bacterial cell wall's outer membrane [53]. Second, producing ROS involves the formation of H 2 O 2 and the release of zinc ions into a bacterium-infested environment, which is toxic [54,55]. An earlier study found that hybrid ZnO NPs had exceptional antibacterial properties, which corroborate the current study's findings [56].…”
Section: Discussionsupporting
confidence: 85%
“…The NPs' activity could be initiated in two ways: by directly or electrostatically interacting with the NPs and causing injury to the bacterial cell wall's outer membrane [53]. Second, producing ROS involves the formation of H 2 O 2 and the release of zinc ions into a bacterium-infested environment, which is toxic [54,55]. An earlier study found that hybrid ZnO NPs had exceptional antibacterial properties, which corroborate the current study's findings [56].…”
Section: Discussionsupporting
confidence: 85%
“…The X-ray diffraction (XRD) was used to analyze the crystal structure of the ZnMOF powder. Figure 1 G showed the XRD patterns of ZnMOF particles, the standard diffraction peaks of which are consistent with the crystalline nature of zinc crystals 43 , suggesting the successful synthesis of ZnMOF with an integral crystal structure. Besides, the absorption profile of the ZnMOF solution also shows a characteristic peak at 430 nm (Figure 1 H-I), consistent with that of curcumin 44 .…”
Section: Resultssupporting
confidence: 54%
“…The maximum absorption depends on the NP morphology, dimensions, and surface microstructure. A broad absorption peak centered at approximately 390 nm was the characteristic of the Semal-ZnO NP formation in the range of 350–400 nm and was attributed to the binding of various capping molecules with the ZnO NPs, resulting in increased bandgap ( Figure 1A ) ( Abdelbaky et al, 2022 ; Sharma et al, 2022 ; Ramesh et al, 2023 ). The absorption peak observed in this study may be attributed to the intrinsic bandgap formed by electron transitions from the valence band (E V ) to the conduction band (E C ) of the Semal-ZnO NPs ( Mageswari et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%